1998
DOI: 10.1046/j.1365-2958.1998.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli genes expressed preferentially in an aquatic environment

Abstract: SummaryEnteric bacteria are frequently found in aquatic environments, where they may pose a risk to human health. Although bacterial survival and persistence in such habitats has been studied extensively, there is almost no information about bacterial adaptation to these conditions at the level of changes in gene expression. As a first exploration of this field, we have carried out a screen designed to identify Escherichia coli genes that show increased expression in an aquatic environment. The screen was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
(42 reference statements)
2
19
0
Order By: Relevance
“…Savageau (1983) suggested that E. coli cells cope with the transition by possessing a dual regulation system, where genes with products in high demand are under positive control, whilst genes with products in low demand are under negative control ; the controls systems alternate depending on the specific demands imposed by the primary and secondary environments. Savageau (1983) presented numerous examples of physiological functions in enteric bacteria that are consistent with the demand theory and it has been demonstrated that, in E. coli, some genes appear to be preferentially expressed in the external environment (Espinosa-Urgel & Kolter, 1998).…”
Section: Abbreviationsmentioning
confidence: 76%
“…Savageau (1983) suggested that E. coli cells cope with the transition by possessing a dual regulation system, where genes with products in high demand are under positive control, whilst genes with products in low demand are under negative control ; the controls systems alternate depending on the specific demands imposed by the primary and secondary environments. Savageau (1983) presented numerous examples of physiological functions in enteric bacteria that are consistent with the demand theory and it has been demonstrated that, in E. coli, some genes appear to be preferentially expressed in the external environment (Espinosa-Urgel & Kolter, 1998).…”
Section: Abbreviationsmentioning
confidence: 76%
“…The amino acid sequence of Alda displays similarities with sequences of several aldehyde dehydrogenases of eucaryotic origin but not with microbial glyceraldehyde 3-phosphate dehydrogenase [30]. Nevertheless, the overexpression of Alda may be compared with recent data obtained by EspinosaUrgel and Kolter [31]. These authors showed that E. coli cells exposed to aquatic environments overexpressed a gene of unknown function, gapC, whose product showed [32].…”
Section: Discussionmentioning
confidence: 93%
“…These authors showed that E. coli cells exposed to aquatic environments overexpressed a gene of unknown function, gapC, whose product showed [32]. In a similar way, Espinosa-Urgel and Kolter speculated that the expression of gapC in organisms exposed to an aquatic environment helps the cells to prepare for the colonization of a new host by contributing to the synthesis of curli [31]. Might Alda accumulation reflect another stress response of the cells?…”
Section: Discussionmentioning
confidence: 97%
“…Such a multiplicity is well known in bacteria (in, e.g., E. coli; Hidalgo et al, 1996;Espinosa-Urgel and Kolter, 1998). In A. fumigatus strain Af293, the second gene (gpdB) [locus AFUA_5G01030] is a pseudogene due to a very recent duplication of 18 bases in the coding area which introduces an in-frame stop codon whereas the deduced amino acid sequence is otherwise identical to that of the GpdB protein from a second A. fumigatus strain, A1163.…”
Section: The C3 Steps Of Glycolysismentioning
confidence: 94%